2012
DOI: 10.1055/s-0032-1311979
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes of Women Receiving Compounded 17 α-Hydroxyprogesterone Caproate for Prophylactic Prevention of Preterm Birth 2004 to 2011

Abstract: Home nurse administration of compounded 17P is safe and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Based on the assumption that only 60% of eligible women used 17OHP-C (9), we would have at least 80% power to see the following differences: for exposure variables with a prevalence of 10%, we could detect a 2.25-fold difference in 17OHP-C use; 20% prevalence, a 1.25-fold difference; 40% prevalence, a 1.5-fold difference; and for 60% prevalence, a 1.5-fold difference.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the assumption that only 60% of eligible women used 17OHP-C (9), we would have at least 80% power to see the following differences: for exposure variables with a prevalence of 10%, we could detect a 2.25-fold difference in 17OHP-C use; 20% prevalence, a 1.25-fold difference; 40% prevalence, a 1.5-fold difference; and for 60% prevalence, a 1.5-fold difference.…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, at the health systems level, women may not be seeking prenatal care at an early enough gestational age to initiate the medication, may have difficulty in obtaining it and arranging weekly administration, or their insurance may not fully cover the medication. (89) In a survey of general obstetrician-gynecologists exploring attitudes regarding the use of 17OHP-C, respondents reported that they prescribed 17OHP-C to only 59% of eligible patients. (10) While evidence regarding the efficacy of 17OHP-C in reducing the risk of recurrent spontaneous preterm birth continues to mount, it is of critical importance to understand what biases affect its use in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arrangements were made for home delivery of unit dose, preservative-free vials of 17OHPC using the specifications and formulation of the 17OHPC used in the Meis et al Network Study including the vehicle (castor oil) [11]. Similar efficacy has been demonstrated between this compounded product and the product approved by the U.S. Food and Drug Administration, Makena (Ther-Rx Corporation, St. Louis, MO) [12]. A nurse and pharmacist were available continually for patient questions and concerns.…”
Section: Methodsmentioning
confidence: 99%
“…One factor that the agency considers in determining whether a drug may be compounded is whether the prescribing practitioner has determined that a compounded product is necessary for the particular patient and would provide a significant difference for the patient as compared to the FDAapproved commercially available drug product" [33]. In addition, the safety and effectiveness of compounded 17-OHPC was confirmed in the pregnancy outcomes study of women receiving for prophylactic prevention of preterm birth [34]. Quality control of the active pharmaceutical ingredients and compounded products of 17 alpha hydroxyprogesterone caproate Further, our stability-indicating study [35] ( Table 4) also demonstrated that 17-OHPC appeared to be fairly stable when exposed for a short term to high temperature, light, strong acid, different preservatives, and different dispensing containers under respective experimental conditions.…”
Section: Fda-approved Product and Compounded Versionmentioning
confidence: 99%